1994
DOI: 10.1007/bf02768287
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy of hydroceles with polidocanol

Abstract: Fifteen patients with hydroceles of the testis or spermatic cord were treated by aspiration and injection of the sclerosant solution polidocanol. The cure rate of hydroceles after one sclerotherapy session was 73%, and the overall cure rate using the procedure was 87%. No patient experienced pain during or after the procedure, which was conducted without anaesthesia. No complications were observed. It is concluded that sclerotherapy of hydroceles with polidocanol may be a useful alternative to open operation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…In the present study the mean hydrocele volume (212.9 ml) is comparable to the mean volume reported in other [3,[5][6][7]. The volume of phenol instilled by us is in accordance with the studies of Shan et al in which volume of phenol instilled was proportional to the volume of the hydrocele [3].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In the present study the mean hydrocele volume (212.9 ml) is comparable to the mean volume reported in other [3,[5][6][7]. The volume of phenol instilled by us is in accordance with the studies of Shan et al in which volume of phenol instilled was proportional to the volume of the hydrocele [3].…”
Section: Discussionsupporting
confidence: 95%
“…However, Sigurdsson et al and Fuse et al have reported higher success rates (67% and 73%, respectively) with a single session of polidocanol sclerotherapy [4,5]. In group 3 (operative treatment), we were able to achieve a 100% cure rate which is similar to the previously reported results [3,13,14].…”
Section: Discussionsupporting
confidence: 92%
“…However, Latif et al [17] in their study among 50 patients of hydrocele found the incidence of bilateral involvement to be 2 % only. Similarly, Fuse et al [18] reported none of their 15 patients to be having bilateral involvement. Agrawal et al [19] also did not report a single case with bilateral involvement.…”
Section: Discussionmentioning
confidence: 89%
“…16,17 Similarly, Fuse et al reported none of their 15 patients to be having bilateral -involvement. 18 Agrawal et al also did not report a single case with bilateral involvement. 19 It is difficult to comment whether all these studies had selected patients with unilateral involvement only, as these studies were comparative studies, and hence, in order to rule out any confounding effect, they might have excluded the bilateral involvement.…”
Section: At Fourth Follow-upmentioning
confidence: 96%